Holiday Inn, Barbados, West Indies. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
This is is a beach side view of the Holiday Inn hotel, the jetty and cabanas. It is a seven storey building with attached balconies. The most visible architectural features of the buildings are the roof work and the windows. On the beach side is a covered section with chairs and tables, as well as beach chairs on the jetty. This is an undivided back postcard. Back of the Postcard Printed in England by Photo Precision Ltd. EPND £8 (Handwritten in Pencil)
Landscape, Color, “3 ½” x 5½”
Keywords: Hotels; Tourists; Tourism; Beaches; Architectural features; Buildings; Roofs; Cabanas